Simulasi Protokol TCP-UDP Pada Jaringan Topologi Bus Menggunakan Simulasi Cisco Packet Tracer - Qonita Auliani; Zada Aulia Munawarah; Muhammad Rizki; Riyan Aditya; Didik Aribowo (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
In this digital era, network speed is very important, because nowadays many people use the internet as a companion in various events. Data communication is one of the means to allow several devices to communicate with each other. To simplify and speed up network usage, the Transmission Control Protocol (TCP) and User Datagram Protocol (UDP) protocols are used as the transport layer during data transfer. In running this simulation using the Cisco Packet Tracer simulation application using bus topology as the topology type.